SPEECH ACTS IN INDONESIA INDEPENDENCE DAY SPEECH - Siti Rahma Ritonga (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
This study is concerned with the use of speech acts in Indonesia Independence  Day Speech. The objective of this study were to describe the types of speech acts of  President’s speech in 72nd Indonesia Independence Day 2017 , the most dominant types of speech act, and to described the reason why the most dominant types of speech acts used by him. This  study was conducted by qualitative anaylisis method. The source of data in this study was Jokowi’s speech in 72nd Indonesia Independence Day 2017, while the  data were taken from his utterances in script of speech. The findings of this study showed that all types of speech acts, namely representative, directive, commissive, expressive and declarative The representative speech acts was the most dominantly used in his speech. The reasons of  Jokowi used the representative speech acts were he could deliver the information about government’s achievements in 2017 and the goals in the next year.